Vivid colours in hyperuniform complex-index photonic structures by resonant interference of photonic band gaps and optical band gaps. Issue 63 (25th October 2018) - Seo, Chunhee; Hyon, Jinho; Suk, Soyeon; Oh, Changjoon; Nam, Jihye; Minh, Duong Nguyen; Sim, Jae Hyun; Kang, Youngjong
Abstract : Hyperuniform photonic structures (HPSs) have been doped with complex index materials to increase their reflectivity and colour expression range. Abstract : Hyperuniform photonic structures (HPSs) have been doped with complex index materials to increase their reflectivity and colour expression range. HPSs synthesized using dielectric SiO2 nanoparticles have been mixed with a small amount of dopant nanoparticles ( c d ≤ 1%) having a complex refractive index. Various dyes including Sudan I, Sudan Blue II, Alizarin yellow GG, Bromocresol purple and polydopamine (PDA) are used as dopants. Large reflectivity enhancements of HPSs (∼100%) are observed by resonant interference of photonic band gaps (PBGs) and optical band gaps (OBGs). Reflectivity enhancements are observed only when PBGs of HPSs match with OBGs of dopants. The colour expression range of HPS increases by 600% by doping with melanine-like PDA nanoparticles, which have the imaginary part of the refractive index in whole visible range.